GAMBARAN QUALITY OF LIFE COMPUTER VISION SYNDROME PADA MAHASISWA FKIK UNIVERSITAS KRISTEN KRIDA WACANA - Santi Anugrahsari; Angela Virgini Tiomegarani; Hansen Wijaya; Mutiara Nur Adinda; Maqhi Suhada (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
Background: Computer Vision Syndrome is a complex eye problem and visual disturbance that occurs due to excessive use of visual screens. Objectives: The purpose of this study was to describe the symptoms of Computer Vision Syndrome (CVS) found in FKIK students at Krida Wacana Christian University through dissemination. Methods: A descriptive study using the Cross-Sectional method. The sampling technique is purposive sampling. Results: The results showed that the duration of use during working hours was 2 hours, the most for 27.5% of subjects. Above 50% of the subjects rarely complained of blinking eyes, burning sensation, crossing their eyes, rarely experienced lighting complaints, and never complained of red eyes. Meanwhile, 30 to 49% of the subjects rarely experienced tired eyes, or eye pain, and never complained of sore eyes, double vision, and sometimes watery eyes. Conclusion: In this study, eye symptoms with computer use were mild and did not interfere with daily activities. It is recommended to research students who routinely use digital media for further research Keywords: Computer Vision Syndrome, Digital media, Symptoms Â